Nomenclatural Notes on Three Celastraceous Species from India - Bennet, S. S. R.; Sahni, K. C. (Indian Forester, 1977)
Two new combinations, Maylenus rothiana (Lawson) Bennet & Sahni and M. wallichii (G. Don). Bennet & Sahni, have been proposed here for the plants commonly known by the names Gymnosporia rothiana Lawson and G. wallichiana Lawson in India Floras. Also a new name, Maytenus kurzii Bennet & Sahni,is proposed for Moytenus thomsonii (Kurz) Raju & Babu because of the earlier name M. thompsonii Fosberg.